Pediatric maxillary and mandibular osteomyelitis - Oré Acevedo, Juan Francisco (2013)
Introduction: Osteomyelitis is a picture of casual presentation, resulting as a complication of various etiologies and requires immediate surgical and medical treatment. Objective: To evaluate the results of pathology-level reported as osteomyelitis of the jaws in pediatric patients , both the jaw and the upper jaw, which required surgical treatment and antibiotic coverage, for the period from 2008 to 2013. Material Methods: Study descriptive, retrospective , held at the National Institute of Child Health Results : predominance was found in males ( 64.7 %) and higher filing under 10 years of age (91%), the mandible was more frequently affected (92.1 %) with a predominance of chronic osteomyelitis in 82.4 % of cases . The region of the mandibular body and angle were the most affected with 75 and 62.5 % respectively. All patients were performed surgical cleaning and removal of sequestra with extractions of compromised parts. Conclusion: Surgery with antibiotic coverage are the mainstay of therapy , which seeks to eradicate the source of infection and the pathogen. We propose as clindamycin antibiotic coverage lactamase resistant penicillin for 8 weeks parenterally for at least 2 weeks and then orally until complete.